2003
DOI: 10.1021/ac026122m
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characterization of Ion Trap Tandem Mass Spectra from Doubly Charged Tryptic Peptides

Abstract: Collision-induced dissociation (CID) is a common ion activation technique used to energize massselected peptide ions during tandem mass spectrometry. Characteristic fragment ions form from the cleavage of amide bonds within a peptide undergoing CID, allowing the inference of its amino acid sequence. The statistical characterization of these fragment ions is essential for improving peptide identification algorithms and for understanding the complex reactions taking place during CID. An examination of 1465 ion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
303
1
11

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(341 citation statements)
references
References 38 publications
23
303
1
11
Order By: Relevance
“…The 'proline effect' describes the intense fragments resulting from cleavage on the N-terminal side of proline residues, but the magnitude by which this cleavage exceeds others is highly dependent upon the residue on the N-terminal side of the bond 11 . Glycine and serine also enhance N-terminal cleavage (to a lesser extent), whereas valine, leucine and isoleucine produce more fragment ions from the bonds at their C-terminal sides 12 .…”
Section: Interplay Of Fragmentation Mechanismsmentioning
confidence: 99%
“…The 'proline effect' describes the intense fragments resulting from cleavage on the N-terminal side of proline residues, but the magnitude by which this cleavage exceeds others is highly dependent upon the residue on the N-terminal side of the bond 11 . Glycine and serine also enhance N-terminal cleavage (to a lesser extent), whereas valine, leucine and isoleucine produce more fragment ions from the bonds at their C-terminal sides 12 .…”
Section: Interplay Of Fragmentation Mechanismsmentioning
confidence: 99%
“…The spectra in each subset were analyzed by a modification of the DaughterDB algorithm. 11 The measures reported for each subset were processed by scripts created in the R statistical environment. 19 …”
Section: Informaticsmentioning
confidence: 99%
“…Our data with the [M Ï© H] Ï© ion of the PRCGVPDVA appear not to be consistent with this view because the selective cleavage occurs at the amide bond between valine and proline, which gives the b 5 ion. However, it has been recently shown that cleavage N-terminal to a proline residue is a very facile process especially when the residue at the N-terminal side of the proline is a valine [24,25]. It seems that sequence context plays a more important role in the fragmentation of the [M Ï© H] Ï© ion of PRC(SO 3 H)GVPDVA than intramolecular ionic interaction between the side chains of acidic and basic amino acid residues.…”
Section: Prcgvpdva Prc(so 2 H)gvpdva and Prc(so 3 H)gvpdvamentioning
confidence: 99%